Political and Economic Forms of Modernity - Allen John; Braham Peter; Lewis Paul (Polity Press - Open University, 1992)
This major introductory textbook examines the political and economic dimensions of twentieth-century industrialized societies. Preface, Introduction, Democracy in Modern Societies, The State in Advanced Capitalist Societies, Political Culture and Social Movements, Citizenship and the Welfare State, Fordism and Modern Industry, The Divisions of Labor and Occupational Change, Work Design and Corporate Strategies, Power and Conflict and Control at Work, Acknowledgements, Index.